2021
DOI: 10.1007/s00425-020-03531-x
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic function of the SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE gene TaSPL14 in wheat plant architecture

Abstract: Main conclusion The function of SQUAMOSA PROMOTER-BINDING PROTEIN-BOX gene TaSPL14 in wheat is similar to that of OsSPL14 in rice in regulating plant height, panicle length, spikelet number, and thousand-grain weight of wheat, but differs during tiller development. TaSPL14 may regulate spike development via ethylene-response gene EIN3-LIKE 1 (TaEIL1), ETHYLENE-RESPONSIVE TRANSCRIPTION FACTOR 2.11 (TaRAP2.11), and ETHYLENE-RESPONSIVE TRANSCRIPTION FACTOR 1 (TaERF1), but not DENSE AND ERECT PANIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 50 publications
3
28
0
Order By: Relevance
“…Many SPL genes are targeted by microRNA156 (miR156), which is an abundant and highly conserved miRNA in plants that regulates the expression of its target genes through transcript cleavage and translational inhibition ( Gandikota et al, 2007 ; Gao et al, 2016 ). While this group of transcription factors tends to be well-conserved across monocot and eudicot plant species ( Wang et al, 2009 ), family members may have distinct functions between species in certain cases ( Preston et al, 2016 ; Gou et al, 2019 ; Cao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many SPL genes are targeted by microRNA156 (miR156), which is an abundant and highly conserved miRNA in plants that regulates the expression of its target genes through transcript cleavage and translational inhibition ( Gandikota et al, 2007 ; Gao et al, 2016 ). While this group of transcription factors tends to be well-conserved across monocot and eudicot plant species ( Wang et al, 2009 ), family members may have distinct functions between species in certain cases ( Preston et al, 2016 ; Gou et al, 2019 ; Cao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…GO analysis of the WAPO1 co-expression network in AABBDD showed that these genes were related to reproductive shoot system development and post-embryonic development (Figure S6A). GSEA results for the network (Figure S6B) also indicated that the network of WAPO1 corresponded to floral transition, in that some gene sets were significantly enriched with reproductive meristem phase change, miR156 miRNA_target_network (miR156 could regulate TaSPL14 and TaSPL17 [60,64]), and SBP TF. After exploring the regulatory regions through motif analysis, we found a novel motif of CArG (CCWWWWWWGG) specifically identified in the promoter region of the WAPO-A1 gene in AABBDD but not in AABB.…”
Section: Case Study: Function Analysis Of Known Gene Wapo1 Using Ccnwheatmentioning
confidence: 84%
“…There are three genes (TraesCS7A02G481600 (WAPO-A1), TraesCS7B02G384000 (WAPO-B1), TraesCS7D02G468700 (WAPO-D1)) in AABBDD; two genes (TRIDC7AG067090 (not expressed), TRIDC7BG060970) in AABB; no gene in AA and one gene (evm.TU.Contig391.11) in DD. We searched the co-expression network of WAPO1 using ccnWheat (Figure 4), and found that spike development related gene wheat FLO/LFY WFL [59], TaSPL14 [60], TaSPL17 [61],…”
Section: Case Study: Function Analysis Of Known Gene Wapo1 Using Ccnwheatmentioning
confidence: 99%
“…Some of the 14 SBP genes in papaya (Carica papaya) are induced at a specific stage in fruit ripening and this process can be controlled by the phytohormone ethylene (Xu et al, 2020). TaSPL14, a close OsSPL14 homolog in wheat (Triticum aestivum), does not regulate the tiller number but binds to the promoters of the ethylene-related genes TaEIL1, TaRAP2.11, and TaERF1 and increases their expression, thereby regulating plant height, panicle length, the spikelet number, and grain weight (Cao et al, 2021). In this study, ABA-responsive elements and stress-responsive elements were found in most of the PgSBP promoters and ABA treatments reduced the expression levels of these genes.…”
Section: Discussionmentioning
confidence: 99%